Aproveitamento de resíduos da biomassa da laranjeira (Citrus sinensis) para geração de bioenergia - Dias, Luciano da Costa (2023)
In the culture of orange (Citrus sinensis), the focus is the production of the fruit, which, when in decline in connection with renewal of the orchards, results in the generation of waste, especially wood, which is not in the roll of biomasses for use in bioenergy. In this sense, the objective was to chemically and energetically analyze the orange wood, produce compacted solid biofuels (briquettes) and verify the quality produced briquettes. In the chemical and energetic characterization were used three compositions, 100% trunk (100T), 90% trunk + 10% bark (90T10B) and 100% bark (100B). The first two compositions were used in the production of briquettes with pressures of 10 and 12 MPa, totaling four types of briquettes named as 100T10P, 100T12P, 90T10B10P and 90T10B12P. The compaction temperature was 90ºC. The 100T composition presented lower extractives value (6.66%), higher lignin and holocellulose content (24.01% and 72.19%) and higher useful calorific value (17.51 MJ.kg -1 ) and the composition 100B presented higher ash content (10.35%). In relation to briquettes produced, apparent density and density by densitometry of xrays was higher in the type of briquette 90T10B12P, 1218 and 1194 kg.m-3 respectively. The briquette 100T10P obtained greater volumetric retraction (3.83%) and the lowest moisture absorption occurred in the 90T10B12P. The briquette 100T12P obtained higher value in the compressive strength test (3.12 MPa), but lower combustion index (0.16). The densification between the pressures used in briquetting was evidenced in scanning electron microscopy (SEM). The orange wood presented chemical and energy composition similar to the biomass for energy purposes and the briquettes produced showed low moisture, mechanical strength and combustibility within the appropriate levels according to the literature.